The Influence of Textured Surfaces of Cosmetic Packaging on Consumers Feelings - Siripuk Ritnamkam; Yada Chavalkul (My University, 2018)
This study investigated what consumers’ feelings were evoked when they touched different textured surfaces of 20 compact powder cases. Without seeing them, fifty respondents with and without an art-and-design-based background were asked to describe their feelings in their words as they touched the cases as well as explain them by provided words. The results show that different surface textures did evoke different respondents’ feelings of which those familiar with the design were able to express a wider range. All participants were able to describe both the initial sense of physicality and complex feelings toward every textured surface investigated.Keywords:senseof touch; textured surfaces; cosmetic packaging; consumers’ feelings.eISSN 2398-4295 © 2018. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open-access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer–review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: http://dx.doi.org/10.21834/ajbes.v3i13.154
Keywords: Association (psychology); Color perception and design